2018
DOI: 10.1002/epi4.12277
|View full text |Cite
|
Sign up to set email alerts
|

How do we use in vitro models to understand epileptiform and ictal activity? A report of the TASK1‐WG4 group of the ILAE/AES Joint Translational Task Force

Abstract: SummaryIn vitro brain tissue preparations allow the convenient and affordable study of brain networks and have allowed us to garner molecular, cellular, and electrophysiologic insights into brain function with a detail not achievable in vivo. Preparations from both rodent and human postsurgical tissue have been utilized to generate in vitro electrical activity similar to electrographic activity seen in patients with epilepsy. A great deal of knowledge about how brain networks generate various forms of epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 131 publications
(148 reference statements)
0
23
0
Order By: Relevance
“…While remain to be verified, these observations suggest that the DHC-mediated bilateral hippocampal connectivity can be at least partly retained at more physiological temperatures. As the use of near physiological temperatures generally decreases the survival time of acutely prepared brain slices (Dulla et al, 2018 ), structural and/or functional deterioration of bilateral hippocampal tissues particularly the connecting DHC at 35–36°C may largely account for the diminished and/variable bilateral hippocampal activities observed. Further works are necessary to improve our experimental conditions and to achieve better preservation of the bilateral hippocampal connectivity at more physiological temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While remain to be verified, these observations suggest that the DHC-mediated bilateral hippocampal connectivity can be at least partly retained at more physiological temperatures. As the use of near physiological temperatures generally decreases the survival time of acutely prepared brain slices (Dulla et al, 2018 ), structural and/or functional deterioration of bilateral hippocampal tissues particularly the connecting DHC at 35–36°C may largely account for the diminished and/variable bilateral hippocampal activities observed. Further works are necessary to improve our experimental conditions and to achieve better preservation of the bilateral hippocampal connectivity at more physiological temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro epileptiform field potentials were recognized according to the recommendations of the International League Against Epilepsy and American Epilepsy Society Joint Translational Task Force (Raimondo et al, 2017 ; Dulla et al, 2018 ). Briefly, ictal-like discharges were considered as repeated spike waveforms with peak amplitudes of ≥1 mV, durations (spike-expressing components of ≥10 s, and mean interevent intervals of ≥90 s. Interictal spike like potentials were recognized as intermittent or periodic events with peak amplitudes of ≥0.5 mV and durations (components with low-amplitude spikes) of ≤1 s. Single- or multi-unit spike activities that displayed base duration of ≤5 ms, variable amplitudes and spikes rates were not considered as epileptiform field potentials because these spikes activities were not uniformly detected in the targeted area.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, unlike other agents such as picrotoxin or bicuculine, this method preserves the local inhibitory network, thus allowing for meaningful assessment of ictal recruitment patterns that are modulated by feedforward inhibition. Previous studies have shown that prolonged exposure to zero Mg 2+ solution produces continuous rhythmic discharges lasting less than one second in duration as opposed to propagating ictal events, giving cause to limit our experiments to 30 min ( Anderson et al, 1986 ; Dulla et al, 2018 ). The major disadvantage of using this chemoconvulsant, however, is that it there is widespread increase in the level of excitatory glutamatergic drive across the slice.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The three priorities in the vision to transform epilepsy research and care were the development of AEG and DM treatments and treatments for drug-resistant seizures and comorbidities. 6 The ILAE/AES Joint Translational Task Force spearheaded an international collaboration of expert working group members who developed proposals for harmonizing the methodology and interpretation of video-electroencephalography (vEEG) studies in rodent models (TASK1), [8][9][10][11][12][13] undertook a systematic review on outcome measures in preclinical epilepsy studies (TASK2), 14 created preclinical epilepsy research common data elements (CDEs) to improve across-studies comparisons, study reporting, and collaborative research (TASK3), [15][16][17][18][19][20][21] and proposed infrastructure for multicenter preclinical trials for epilepsy therapy development (TASK4). 22…”
Section: International League Against Epilepsy (Ilae) and The American Epilepsy Society (Aes)mentioning
confidence: 99%